Regional unemployment and new economic geography - Ulrich Zierahn (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2011)
Regional labor markets are characterized by huge disparities. The literature on the wage curve argues that there exists a negative relationship between unemployment and wages. However, this literature cannot explain how disparities of these variables between regions endogenously arise. In contrast, the New Economic Geography analyzes how disparities of regional goods markets endogenously arise, but usually ignores unemployment. Therefore, this paper discusses regional unemployment disparities by introducing efficiency wages into the New Economic Geography. This model shows how disparities of regional goods and labor markets endogenously arise through the interplay of increasing returns to scale, transport costs and migration.
Keywords: J64; R12; R23; 330; regional unemployment; new economic geography; core-periphery; wage curve; labor migration